Pulse density modulated control patterns for inductively powered implantable devices based on energy injection control. Issue 6 (1st July 2013) - Leung, Ho Yan; McCormick, Daniel; Budgett, David M.; Hu, Aiguo Patrick
Abstract : High power inductively powered implantable devices (5–15 W) such as an artificial heart demand continuous power over widely varying coupling and loading conditions. An energy injection converter is suitable for driving the power transfer coil of an inductive power transfer system for this application because of its ability to control power flow over a large coupling range without any additional power stages. In addition it allows this to be done while maintaining soft‐switching at all times. Here the authors propose a new control method based on pulse density modulation patterns. The proposed control is compared with other energy injection control methods, and it is found to have superior performance in terms of control action and linearity. It is also shown to improve the practical control range and decreases the component stress with improved resonant waveforms. The comparison of different control methods was performed through simulation and verified through practical implementation.